EVALUATION OF INFILL BUILDING BLOCK IN HERITAGE SCHOOLS IN KUALA LUMPUR - Zamri, Mohd Amirul Hakim; Abdullah, Jamalunlaili (PLANNING MALAYSIA, 2018)
In Kuala Lumpur, there are a few heritage schools that are more than 100 years old which have experienced significant infill developments since colonial era. This study evaluates the infill building structures and proposes a suitable design approach of infill development in heritage school. It focuses on the infill development theory, reviews on the physical aspect of heritage school buildings as well as related local policies and guidelines. In order to achieve the research purpose and objectives, the study uses the qualitative methodology. The study found that there are 2 infill design approaches, which is the complementary design approach and contrast design approach and both can be used as long as compatible and in harmony with the existing heritage building and site. Through site observation survey, it was found that although infill development at St John’s Institutions and Maxwell Secondary Schools adopted the contrast approach, the outcome were different. Infill development at St John’s Institutions was compatible and in harmony, while at Maxwell Secondary School was the opposite. Therefore, this study suggests improvement on the existing infill structures in the heritage school, either through image restoration or transfer of facilities to future development. Other recommendation include the government providing infill development guidelines for heritage site, encouraging private sector to participate in heritage school conservation and development, and controlling the height of new development within 100 meter radius from heritage buildings.